Exploring actual and perceived levels of physical activity intensity during virtual reality active games - Naugle, Keith E.; Cervantes, Xzaliya A.; Boone, Carolyn L.; Wind, Brandon; Naugle, Kelly M. (Frontiers in Sports and Active Living, 2024)
Background: Research suggests that active virtual reality (VR) video games can elicit light to moderate physical activity (PA) and thus, could be a novel and fun mode of exercise. More research is needed to understand the influence of VR on perceptions of exertion and enjoyment during PA. Objective: The purposes of this study were 1) to compare actual and perceived exertion within and between active VR games with varying levels of difficulty, and 2) to determine how playing active VR games influence PA enjoyment during gameplay. Methods:Eighteen participants completed four separate study sessions, in which a 15-minute bout of traditional exercise (stationary cycling) or one VR game was played. Heart rate (HR) and ratings of perceived exertion (RPE) using Borg's CR10 scale were assessed during VR gameplay and cycling. Enjoyment was measured after gameplay. VR games included playing Holopoint at level 2 and level 3 and Hot Squat. Repeated measures ANOVAs were used to examine 1) changes in HR and RPE across time within games and 2) differences in actual and perceived intensity and enjoyment between games. Bivariate correlations examined the relationship between the degree of change in actual intensity and the degree of change in perceived intensity during each VR game and cycling. Results: The analyses revealed that RPE and HR significantly increased from baseline during each condition, and generally increased across the 15-minutes of gameplay. Hot Squat and cycling elicited significantly higher percentage of heart rate reserve (%HRR) than Holopoint at level 2 and 3. Holopoint level 3 elicited higher %HRR than Holopoint level 2. Participants reported greater average and max RPE during Hot Squat and cycling compared to Holopoint at level 2 and 3. The correlations showed a significant positive correlation between the degree of change in HR and RPE for cycling, but no significant correlations for any of the VR conditions. Physical activity during Holopoint at both levels was rated as more enjoyable than Hot Squat and cycling. Conclusion: Our data supports the notion that VR may alter perceptions of exertion during PA, and in particular, may dampen the awareness of increases in actual exertion.